2008
DOI: 10.1097/opx.0b013e31818e8d57
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Refractive Index of the Human Lens upon Accommodative Response

Abstract: Gullstrand suggested that there would be an increase in the equivalent refractive index with accommodation; the intra-capsulary mechanism of accommodation. However, we found that the equivalent refractive index of the lens does not change with accommodation when the accommodative lag is taken into account. Furthermore, it appeared to be possible to simulate the accommodative process of a subject with a two-compartment model with constant refractive indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 9 publications
4
37
1
Order By: Relevance
“…036 63 In agreement with previous findings, we have found that a rather constant value of the parameters defining the GRIN best fitted the experimental data 9,35 and that the equivalent refractive index did not change with accommodation. 9,34,35 Despite the simplicity of the GRIN model, the estimated parameters allow reproducing the experimental input data with great accuracy (mean RMS < 40 lm), for all accommodation levels, using our recently developed optimization method based on OCT imaging. 28 Previous studies with simpler GRIN models suggested that no change in the parameters of the model was needed to account for a change of power of the crystalline lens with accommodation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…036 63 In agreement with previous findings, we have found that a rather constant value of the parameters defining the GRIN best fitted the experimental data 9,35 and that the equivalent refractive index did not change with accommodation. 9,34,35 Despite the simplicity of the GRIN model, the estimated parameters allow reproducing the experimental input data with great accuracy (mean RMS < 40 lm), for all accommodation levels, using our recently developed optimization method based on OCT imaging. 28 Previous studies with simpler GRIN models suggested that no change in the parameters of the model was needed to account for a change of power of the crystalline lens with accommodation.…”
Section: Discussionsupporting
confidence: 80%
“…33,34 The relative contribution of the GRIN to lens power appears to remain constant with accommodation. 9,34,35 This suggests that a homogenous index material in lens refilling procedure would be equally efficient in producing a refractive power change (assuming identical lens shape changes) than the natural lens GRIN material. However, the impact of the GRIN in the lens high order aberrations and their change with accommodation has never been studied experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…The corneal refractive index was taken as 1.376, the aqueous humor refractive index as 1.336, and the crystalline lens refractive index was obtained from the age-dependent average refractive index expression derived by Uhlhorn et al (1.4104-1.4113 for the subjects of our study) [42]. A constant refractive index was used for all the accommodative demands since the equivalent refractive index does not change significantly during accommodation [43,44]. Optical distortion correction by the corneal surfaces (for the anterior lens) and corneal and anterior lens surfaces (for the posterior surface) were corrected using 3-D ray tracing routines, as described by Ortiz et al [30].…”
Section: Image Processingmentioning
confidence: 99%
“…63,65 Different types of GRIN distributions yield totally different predictions 27,29 of optical performance. More recent studies, 68,69 suggest that the contribution of the GRIN distribution to the optical performance of the eye may be modest compared to earlier assumptions.…”
Section: Model Predictionsmentioning
confidence: 95%
“…In this case, the actual contribution of the GRIN structure will be much lower. A recent study by Hermans et al 68 suggests that the impact of the GRIN structure is modest. These authors even claim that they can model accommodation with a simple lens model under the assumption that both cortex and nucleus have different but homogeneous refractive indexes.…”
Section: Power (D) Model Fit Error (μM)mentioning
confidence: 99%